The Relationship Between Student Learning Interest, Achievement Motivation and Student Parents ' Support for UMKT Sports Education During the Pandemic on Student Learning Outcomes: Hubungan Antara Minat Belajar Mahasiswa, Motivasi Berprestasi dan Dukungan Orang Tua Mahasiswa Pendidikan Olahraga UMKT Selama Pandemic Terhadap Hasil Belajar Mahasiswa - Nanda Alfian Mahardhika; Jeane Betty Kurnia Jusuf; Januar Abdilah Santoso; Bimo Alexander; Ahmad Nuruhidin (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
The research has several objectives, namely wanting to know the relationship between student interest in learning to learning outcomes, knowing the relationship of motivation for achievement to learning outcomes, knowing the relationship between parental support to learning outcomes, knowing the relationship between student interest in learning, learning achievement and parental support for learning outcomes of Sports Education (POR) students of the University of Muhammadiyah East Kalimantan (UMKT). The design of the research carried out is correlation. The population in this study was 64 students of the UMKT POR Study Program and a sample of 30 people with purposive sampling techniques with data analysis looking for the percentage of each indicator. This study obtained the results of contributions from each variable that the contribution of student interest in learning is high, the motivation for achievement is in the medium category, and the support of parents in the high category so that the relationship between interest in learning, motivation for achievement and parental support is in the high category. The benefits of the research are known that the interest in learning, motivation and support of parents of POR UMKT students are very supportive of learning outcomes even during a pandemic